Comparison of pork carcass evaluation procedures - D Stiffler; Donald H Kropf (Kansas Agricultural Experiment Station Research Reports, 1970)
Carcass data were obtained from 28 barrows from the Kansas Swine Testing Station and 31 from the Kansas State Barrow Contest in 1969. All were slaughtered and standard measurements taken. Each carcass was cut to wholesale cuts by the conventional K.S.U. lab method. Cut-out data were used to calculate ham-loin index, four lean-cut percentages (live and carcass weight), percent ham plus loin of live and carcass weight, and dollar value of five wholesale cuts per hundred weight of carcass.; Swine Day, Manhattan, KS, October 1, 1970
Keywords: Swine day; 1970; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 163; Swine; Pork carcass; Price of cuts